Analisis Struktur Komparatif Industri Pada Perkembangan Industri - Virgi Ainun Iqbal; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This paper analyzes the comparative structure of industry in Indonesia. The paper discusses the factors that influence industrial development and formulates strategies to promote sustainable industrial growth. Analysis of the comparative structure of the industry is important to understand the dynamics of the industry and identify future opportunities and challenges. This paper also discusses strategies to encourage sustainable industrial growth, such as increasing investment in education and training, building adequate infrastructure, implementing policies that support industry, increasing the use of technology, and promoting local products and services.